The Name of the Uzbek Language in History (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is based on scientific and artistic sources, discusses the formation and development of the Uzbek language as an independent language, separate from the Turkic language, the formation of its lexical layer, the terms by which it was named in different centuries, and the lexical meanings of these terms.